2004
DOI: 10.1590/s0004-27302004000500007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular genetics of primary pigmented nodular adrenocortical disease

Abstract: Carney complex (CNC) is a multiple endocrine neoplasia (MEN) syndrome associated with other, non-endocrine manifestations such as lentigines, cardiac myxomas and schwannomas. Primary pigmented nodular adrenocortical disease (PPNAD), leading to corticotrophin-independent Cushing's syndrome is the most frequent endocrine lesion in CNC. The complex has been mapped to 2p16 and 17q22-24, although additional heterogeneity may exist. The gene coding for the protein kinase A (PKA) type I-a regulatory subunit (RIa), PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In studies on autopsies of patients with CNC, PPNAD was observed in almost all cases. 4,10,11 Although our patient presented a classical picture of Cushing's syndrome, her two-year history of amenorrhea, which was thought to have been caused previously by PCOS, and her short stature could be indicative of a disease that emerged atypically a long time earlier.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In studies on autopsies of patients with CNC, PPNAD was observed in almost all cases. 4,10,11 Although our patient presented a classical picture of Cushing's syndrome, her two-year history of amenorrhea, which was thought to have been caused previously by PCOS, and her short stature could be indicative of a disease that emerged atypically a long time earlier.…”
Section: Discussionmentioning
confidence: 78%
“…9 PPNAD is a rare form of ACTH-independent Cushing's syndrome that may occur alone, but is found to be associated with CNC in 90% of the cases. 10 It is the most common endocrinal hyperactivity in these patients, and has been described in 25% of them. This incidence, however, is probably an underestimate, because of untypical and subclinical cases, and the cycles of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous myxomas are also seen on the eyelids and in the external ear canals. 1,7 Presence of 2 or more of these manifestations, including PPNAD, are required to make the diagnosis. 8 PPNAD is the most frequent and characteristic endocrine tumor observed in CNC.…”
Section: Discussionmentioning
confidence: 99%
“…Primary pigmented nodular adrenocortical disease (PPNAD), a rare cause of ACTHindependent Cushing syndrome, is the main endocrine manifestation of Carney complex (1,2). Mutations of the gene encoding protein kinase A regulatory subunit 1α (PRKAR1A) represent the molecular aetiology of approximately 41% of the kindreds affected by Carney complex (3)(4)(5)(6). Additionally, genetic linkage analysis has identifi ed other genetic loci on chromosome 2p in families with Carney complex (7,8).…”
Section: Introductionmentioning
confidence: 99%